Restrukturisasi Kredit Perbankan Sebagai Upaya Penyelamatan Kredit Bermasalah Pada Masa Pandemi Covid-19 - Esther Masri; Sri Wahyuni (KRTHA BHAYANGKARA, 2022)
Restructuring is an effort to save non-performing loans because debtors have difficulty in fulfilling their obligations (default). The government through the Financial Services Authority Institution has asked banks to carry out an inventory of debtors affected by Covid-19 and provide a credit restructuring policy during the Covid-19 pandemic, which aims to enable the public, especially debtors, to apply for waivers in making credit payments. Restructuring is provided by creditors to help debtors from debt problems because the debtor has defaulted on the bank credit agreement. The purpose of this study is to determine the implementation and implementation of bank credit restructuring as an effort to rescue non-performing loans during the Covid-19 pandemic. In this study, the author uses a normative juridical research method sourced from a literature study by analyzing the provisions of the legislation. The debtor has the right to apply for credit restructuring if in fact the debtor is in default in making debt payments. However, there are still many applications for credit restructuring, which are carried out by debtors who do not have good intentions on the pretext of being affected by the Covid-19 pandemic even though they still have the ability to fulfill obligations. The success of the implementation of restructuring lies in the intentions and desires of the parties, namely debtors and creditors, must have good intentions in resolving non-performing loans.